Study of pectin extraction from pedada fruit and kepok banana peel - Jariyah Jariyah; Ely Kurniati; Silvana Dwi Nurherdiana (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2022)
This work represents a comprehensive analysis of pedada fruit (Sonneratia caseolaris) as a less desirable fruit, but valuable content such as pectin which obtained through extraction using microwave assisted extraction (MEA) method. Pectin is a water-soluble fiber widely used as a functional component in the food and pharmaceutical industry. The analysis focuses on the comparison profile of pectin from pedada fruit and Kepok banana peel. In addition, the effect of the concentration of the extracting solvent on the methoxyl levels of pectin was also evaluated using the chemometric method (partial least square (PLS) and principal component analysis (PCA)). PLS was performed to determine the methoxyl content which plays a role in determining the pectin type. While PCA was to determine the pectin classification pattern based on the fruit supply location and the extracting solvent. The results showed that the PLS of extracted pectin of pedada fruit and Kepok bananas peels showed an R2 value of 1. This means that the pectin data model of each sample using the MAE method was in good classification. In addition, the PCA results show that the pectin extraction data plots are close together between samples in the quadrant, indicating the same characteristics and quality of pectin.